Pyroclastic Density Current Facies in the Millennium Eruption of Tianchi Volcano, Northeast China: Insights From Topography, Stratigraphy, Granulometry, and Petrography - Zhao, Bo; Xu, Jiandong; Yu, Hongmei; Chen, Zhengquan (Frontiers in Earth Science, 2020)
Large-scale pyroclastic density currents (PDCs) produce inhomogeneity of distributions, thicknesses, stratigraphic structures, and temperatures, thereby causing poor understanding of PDC emplacement processes. Millennium Eruption (ME) of Tianchi volcano in 946 A.D. produced masses of PDCs, covering an area of more than 1570 km2 around the caldera in the Chinese territory. To understand PDC emplacement processes, we examine the proximal to distal variations in the PDC facies during the ME by analyzing the topography, stratigraphy, granulometry, and petrography. The topography of Tianchi volcano has different slopes, including the cone (> 6°), lava shield (2–5°) and lava plateau (< 1°), which affected the PDC emplacement during the ME. The shape of the PDC deposits radiates outward from the caldera, and the periphery has two pyroclastic aprons. The proximal strata (< 10 km) are less than 4 m thick and consist of eutaxitic and lava-like structures in the gullies of the cone. The medial strata (10–20 km) are 10–60 m thick, with columnar joints, pumice-rich layers, and lithic-rich layers in the valleys of the shield. The distal strata (> 20 km) are less than 10 m thick, with coarse-tail layers, ground surge layers, climbing layers, and carbonized woods in the plateau. From the proximal to the distal strata, the emplacement temperature of the PDCs decreased from 740 to 280°C. The medial layers indicate a gravitational differentiation effect and weakened transportation, which led to the formation of thick beds. The distal PDCs demonstrate fluidization characteristics and a density lower than that of the proximal and medial strata, which exhibit clear stratification. Grain size data (< 64 mm) show that the median diameters decreases with increasing distance from the caldera. Rhyolitic and trachytic pumice were found and are assumed to be associated with the composition of the magma chamber. Magmatic mixing structures were confirmed through microscope observations. The volume of the PDCs in the Chinese territory is approximately 7 km3. Our results assist in unraveling some PDCs emplacement processes, marked by a high level of topography confinement, about 50 km runout distance, 280–750°C emplacement temperatures, and more than 7 km3 volume, which provide insights of the PDCs destruction during the ME.